Use and management of technological tools in virtual education for teaching english as a second language - Romero Chávez, Roberto Iván
The covid-19 pandemic brought about major global changes in most aspects of human endeavor. Thus, education and the teaching-learning process took several unexpected turns, which made it necessary for teachers to be trained to face these new challenges that this situation presented. Both educators and students had to adapt to these new conditions, including using different tools, platforms, virtual sites, online classes, and different resources to design and manage didactic material for virtual environments. This report will explain how was the process of specialization of English language teaching for virtual environments, developed in the department of foreign languages at the University of El Salvador through three stages or modules and thus, through the exercise of teaching create the right conditions to take full advantage and effectively some of the resources available on the web and thus impact positively in the educational field, especially for future students served by professionals of the Bachelor Of Arts In English with Emphasis on Teaching.